Manipulative Techniques in Media Texts: A Case Study of Russian-Language Media in Kazakhstan - M. T. Shakenova; M. B. Aitmagambetova (Научный диалог, 2024)
The article explores the methods of manipulation of consciousness in the mass media on the example of content analysis of Kazakhstan Russian-language sources. The authors reveal the concept of manipulation. Media manipulation is carried out at different levels - informational and emotionally expressive according to the two leading functions of the media language: information and impact. In accordance with this, the manipulation is realised at the level of information or expression. Examples of information manipulation through the expansion of information about the described object by including additional, metacommunicative and modified information are given. Another level of manipulation in the media is emotional and expressive influence. Such manipulation is based on labelling, appealing to authority, the interests of ordinary people, appealing to values, traditions, the use of associative binding, false comparisons, false alternatives, exploitation of slogans, conspiracy theories, myths, ridicule and other techniques. According to the authors, the use of media manipulation techniques generates cognitive tension when understanding additional meaning, which leads to a change in the attitude, evaluation and emotional perception of information on the part of the audience.